2011
DOI: 10.1021/nl201821j
|View full text |Cite
|
Sign up to set email alerts
|

Metallic and Insulating Interfaces of Amorphous SrTiO3-Based Oxide Heterostructures

Abstract: The conductance confined at the interface of complex oxide heterostructures provides new opportunities to explore nanoelectronic as well as nanoionic devices. Herein we show that metallic interfaces can be realized in SrTiO 3 -based heterostructures with various insulating overlayers of amorphous LaAlO 3 , SrTiO 3 and yttria-stabilized zirconia films. On the other hand, samples of amorphous La 7/8 Sr 1/8 MnO 3 films on SrTiO 3 substrates remain insulating. The interfacial conductivity results from the formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

40
491
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(532 citation statements)
references
References 28 publications
40
491
1
Order By: Relevance
“…Thus alternative models should explain why the q2DES appears only at a critical thickness. This is quite important, since this feature clearly distinguishes the mechanism of formation of a conducting system in epitaxial LAO/STO from the recent reports of conductivity at amorphous/STO interfaces [52]. For amorphous/STO interfaces there is no clear critical thickness and the interfaces become insulating after annealing in O 2 , so that for these systems oxygen vacancies are the most plausible explanation of the phenomenon [53].…”
Section: Other Mechanismsmentioning
confidence: 91%
“…Thus alternative models should explain why the q2DES appears only at a critical thickness. This is quite important, since this feature clearly distinguishes the mechanism of formation of a conducting system in epitaxial LAO/STO from the recent reports of conductivity at amorphous/STO interfaces [52]. For amorphous/STO interfaces there is no clear critical thickness and the interfaces become insulating after annealing in O 2 , so that for these systems oxygen vacancies are the most plausible explanation of the phenomenon [53].…”
Section: Other Mechanismsmentioning
confidence: 91%
“…This mechanism, along with the polar distortion and dipole screening in the LAO overlayers [16], can qualitatively explain the transport properties. In addition, factors like oxygen vacancies [17][18][19] and cation mixing [20][21][22] may influence the characteristics of the electron gas [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…have recently found that an increased ion bombardment via the laser plume results in an increased reduction10. Another explanation often found in literature is the oxidization of the growing thin film by the STO substrate, eventually resulting in the reduction of the substrate293031. However, as soon as the plume is turned off one would expect the oxygen content of the sample to approach the equilibrium value and thus to reoxidize at a certain rate within the PLD chamber21.…”
mentioning
confidence: 99%